Evaluation of Hospital Sustainability Initiatives in South-east Asia - Nurfikri, Ari; Purwana, Rachmadhi; Soesilo, Tri Edhi Budhi; Danial Kesa, Deni (Poltekkes Kemenkes Surabaya, 2025)
The increasing growth of hospitals in South-east Asia has not been in line with awareness and commitment to sustainability in healthcare facilities. Hospitals play an important role in maintaining public health and contributing to environmental sustainability. However, due to the region's vulnerability to the impacts of climate change, hospitals in South-east Asia have not yet fully transformed into green healthy hospital. This study compares the sustainability of each hospital in South-east Asia that is a member of the Global Green Healthy Hospital (GGHH) based on ten sustainability agendas. This study employs secondary data analysis sourced from the official GGHH website and utilises descriptive quantitative design techniques that include frequency and percentage calculations. The highest percentage of sustainability agenda implementation in the South-east Asia region is waste (72.3%), energy (63.49%), and leadership (52.48%). The lowest percentages are transportation (16.77%), pharmacy (24.92%), and chemicals (31.20%). Hospitals in South-east Asia show a low level of awareness about the implementation of green and healthy hospital practices. Only two countries, the Philippines and Indonesia, have healthcare facilities capable of implementing ten sustainability agendas.